Macronutrients and iron speciation on southern Brazilian continental shelf in summer 2015 - Camila Fiaux Sukekava; Carlos Francisco Ferreira de Andrade; Mônica Wallner-Kersanach; Iarema Carvalho; Leonardo Contreira; Kayla Lima; Mariele Paiva; Daniel Costa; Gabriel Karagiannis Souza; Luis Felipe Hax Niencheski; Luis Miguel Laglera (PANGAEA, 2023)
In summer 2015, The RV Atlântico Sul cruise collected water column samples for macronutrients, dissolved iron (DFe) concentrations and speciation and humic substances (HS) in a transect over the shelf of the South Brazil Bight (SBB) at Santa Marta Grande Cape (28.5°S, SE Brazil) during coastal downwelling episode. Samples were collected over the whole shelf and the initial section of the slope. All samples were collected using 12-liter Teflon-coated Go-Flo bottles suspended on a Kevlar line. Samples were divided into nutrients and trace metals onboard. Samples for nutrients were filtered through 0.45 μm filters (cellulose acetate, Millipore), and samples for dissolved DFe, organic iron speciation and HS were immediately filtered by 0.2 μm (cellulose nitrate ,Millipore). All samples were immediately frozen for analysis. In laboratory, samples were thawed and analyzed for nutrients the analytical methodology used was described in Strickland and Parsons, (1972). DFe concentrations, the samples were determined following a well-established CSV method (Laglera et al., 2013) adding a UV digestion step. Organic iron speciation was analyzed using a modified method described initially by (van den Berg, 2006), but modified removing the addition of bromate from the original method to avoid any underestimation of the contribution of HS to ligand concentrations (Laglera et al., 2011). The determination of HS concentrations and iron-humic complex concentrations following stablished CSV procedures (Laglera et al., 2007; Sukekava et al., 2018). Using those samples, the aim of this research was comprehending the effect of coastal downwelling such episodes in the distributions of macronutrients, DFe and humic substances in SBB.